2016
DOI: 10.5958/0975-6906.2016.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein content in wild and cultivated taxa of lentil (Lens culinaris ssp. culinaris Medikus)

Abstract: The protein contents in 72 diverse accessions of lentil ranged from 10.5 to 23.7 % with an average of 18.7 % in varieties/breeding lines, 14.5 to 27.1 % with an average of 22.4 % in landraces of Mediterranean origin and 18.1 to 32.7 % with an average of 22.6 % in wild species. Significantly high protein content (32.7 %) was recorded in accession ILWL 47 belonging to Lens ervoides. The coefficient of variation and standard deviation in Mediterranean landraces (18.1 %) showed high protein contents as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…Kumar et al. (2016) studied protein content on various species of lentil. They showed that protein content of cultivated lentils had an average of 18.7% (range of 10.5–23.7%) compared with the wild species, which had an average of 22.6% protein content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al. (2016) studied protein content on various species of lentil. They showed that protein content of cultivated lentils had an average of 18.7% (range of 10.5–23.7%) compared with the wild species, which had an average of 22.6% protein content.…”
Section: Discussionmentioning
confidence: 99%
“…Hawtin, Rachie, and Green (1977) reported a wider range, 23.4-36.4%, for protein content when a large set of germplasm (n = 1,688) was screened. Later, Kumar, Singh, Kanaujia, and Gupta (2016) also reported large variability of seed protein among the cultivated lentils. Seed protein of lentil is an important nutritional trait that has particular meaning for the food industry.…”
Section: Crop Sciencementioning
confidence: 94%
“…A subsequent evaluation reported an even wider range when a larger germplasm set (1816 accessions) was investigated [14]. Kumar et al [15] reported a lower average protein content for lentil with broader variability among lentil species.…”
Section: Protein Contentmentioning
confidence: 99%
“…However, a much wider range (18.1%–32.7%) for protein content was reported recently for L. orientalis , L. tomentosus , L. odemensis , L. ervoides , and L. nigricans . The highest protein content was found in the L. ervoides accession, ILWL 47, with 32.7% protein content [15]. L. ervoides accessions also showed the highest variation compared to other studied species.…”
Section: Wild Lentil Taxa Protein Propertiesmentioning
confidence: 99%
See 1 more Smart Citation